Rheumatoid arthritis: frequency of hospitalization and evaluation of economic burden - A. Ciocci; L. Buratti; G. Coari; M. Di Franco; A.M. Iagnocco; M.T. Mauceri; A. Serio (Reumatismo, 2001)
About 10% of the Italian general population is affected by rheumatic diseases (RD). Due to their chronic and disabling nature, RD are cause of an annual economic burden evaluated in about 17,000 billions italian lire. In Italy, rheumatoid arthritis (RA) affects nearly 400,000 people. One hundred RA patients answered to a questionnaire concerning hospitalization during the first ten years of disease. Seventy-two patients needed hospitalization with a total of 147 hospital admissions. Eleven patients were admetted thrice to the hospital, 53 patients twice, and 8 patients only once with a mean number of hospital admissions per patients of 1.8. Hospitalization costs were calculated on the basis of the cost of the DRG for RA and inferred for the total population of Italian RA patients. The result was about 350 billions italian lire. Two methods were used in order to evaluate the economic impact of RA including both direct and indirect costs. First, internationally accepted criteria for cost assessment were applied to the Italian system. Second, different evaluations were performed by the authors. With the first method, direct and indirect costs were 3,000 and 3,500 billions Italian lire, respectively. With the second method, based on a more precise assesment of costs including the costs of wager from a reduction or cessation of work, the total costs for RA was between 3,100 and 3,600 billions Italian lire. Since psychological and social problems often influence patients with RA in relation to their families and society, the issue of intangible costs has also been addressed.